Sociodemographic Study of Posterior Circulation Stroke Survival (Journal of Chittagong Medical College Teachers' Association, 2010)
Key words: Stroke; posterior circulation; sociodemography DOI: 10.3329/jcmcta.v20i1.4930 Journal of Chittagong Medical College Teachers' Association 2009: 20(1):23-26